2017
DOI: 10.1188/17.cjon.309-313
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Standards: Defining the Advanced Practice Role in Genetics

Abstract: Because knowledge concerning genetics and genomics and its application to oncology care is continuing to grow, oncology nurses must be aware of appropriate advanced scope of practice roles based on education and training. All nurses must develop and maintain knowledge of the field, but advanced practice nurses working in genetics have additional competencies and management expectations. Collaboration among practice levels and disciplines is essential. This article focuses on the advanced practice role as furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Advanced practice nurses with knowledge in genetics qualifies the care and access of people at risk or of patients diagnosed with cancer. It is through oncogenetic counseling that the APN acts in an educational manner, provides support to patients and family members, interprets test results and/or diagnostic tests, among others (50) .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced practice nurses with knowledge in genetics qualifies the care and access of people at risk or of patients diagnosed with cancer. It is through oncogenetic counseling that the APN acts in an educational manner, provides support to patients and family members, interprets test results and/or diagnostic tests, among others (50) .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, in the context of genetics/genomics, the nurse acts as an integral member of the interdisciplinary team regarding health care that is based on genomics and comprises diagnosis, prevention, and treatment. Advanced practice nurses, through oncogenetic counseling, act in an educational way, offer support to patients and families, interpret test results and/or diagnostic exams (27) . Regarding political issues (institutional and within the scope of the health system) and insertion in decision-making spaces, it is observed that nurses have the potential to assume responsibilities in the area of management, being able to develop competencies to occupy positions in decision-making environments and of political propositions (28) .…”
Section: 2%mentioning
confidence: 99%
“…Further, they have limited self-assurance in using genomic information as they care for their patients (Jenkins et al, 2015). Similar deficits have been observed among nurse practitioners and physician assistants (Johnson et al, 2017;Kerber & Ledbetter, 2017). Despite the development of educational resources and programs for nurses and other healthcare providers (Campion et al, 2019), there remain gaps in knowledge among these individuals with many lacking genomic literacy and confidence in incorporating genomic information into healthcare practice (Anderson et al, 2015;White et al, 2020).…”
Section: Introductionmentioning
confidence: 95%